Proceedings of the 12th International Conference on Supercomputing 1998
DOI: 10.1145/277830.277874
|View full text |Cite
|
Sign up to set email alerts
|

Predicated array data-flow analysis for run-time parallelization

Abstract: This paper presents a new analysis for parallelizing compilers called predicated array data-flow analysis, whereby array dataflow analysis for parallelization and privatization is extended to associate predicates with data-flow values. These predicates can be used to derive conditions under which dependences can be eliminated or privatization is possible. These conditions, which can consist of arbitrary program statements, can be used both to enhance compile-time analysis and to introduce run-time tests that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Predicated dataflow analysis [22] introduced the idea of using propositional logic predicates over runtime values to derive so-called optimistic dataflow values guarded by predicates. Such analyses are capable of producing multiple analysis versions and keeping them distinct during analysis much like our A3 and A4 analyses.…”
Section: Related Workmentioning
confidence: 99%
“…Predicated dataflow analysis [22] introduced the idea of using propositional logic predicates over runtime values to derive so-called optimistic dataflow values guarded by predicates. Such analyses are capable of producing multiple analysis versions and keeping them distinct during analysis much like our A3 and A4 analyses.…”
Section: Related Workmentioning
confidence: 99%
“…Earlier, disabling infeasible dead statements has been exploited to improve the precision of constant propagation [29] by essentially running a deadcode analysis capable of tagging statements as executable or non-executable during constant propagation analysis. Predicated dataflow analysis [22] introduced the idea of using propositional logic predicates over runtime values to derive so-called optimistic dataflow values guarded by predicates. Such analyses are capable of producing multiple analysis versions and keeping them distinct during analysis much like our A3 and A4 analyses.…”
Section: Related Workmentioning
confidence: 99%
“…These predicates are returned to the programmer for evaluation (for interactive compilation). Further research [6,7,5,2,13] showed how to extract simple scalar conditions from relatively simple array data dependence predicates for a limited number of cases.…”
Section: Automatic Parallelization -Current State Of the Artmentioning
confidence: 99%